A Simple Method for Clearing and Staining Specimens for The Demonstration of Animal Skeleton - Muhammad Ja’far Luthfi; Nyoman Puniawati Soesilo (Biology, Medicine, & Natural Product Chemistry, 2019)
Teaching skeletal system would be more attractive using real/preserved specimen compared to those using only book. The aim of the research was to develop clearing and staining method of animal skeleton specimen using Alizarin Red S-Alcian Blue as teaching aid tool. The specimen were eviscerated, fixed, stained, cleared, and keep in glycerine solution. The spesimen will increase effectiveness in elementary school science teaching and learning.